Análisis de alternativas de intervención que incrementen la relación beneficio-costo (B/C) sobre una vía rural (2017)
"This paper presents a case study of a rural way in the department of Boyacá, Colombia, where the benefit - cost index can be determined by the different intervention alternatives in a tertiary pathway. It intends to visualize the policies and programs developed at international, national and regional level, identifying their sucesses and deficiencies for the sustainable maintenance of roads in our country, the latent need to establish public policies for systemic investment in the tertiary network to achieve articulation with other modes of transport and innovation in the funding mechanisms for these corridors." -- Tomado del Formato de Documento de Grado.